2011
DOI: 10.1073/pnas.1100160108
|View full text |Cite
|
Sign up to set email alerts
|

Smad6 promotes neuronal differentiation in the intermediate zone of the dorsal neural tube by inhibition of the Wnt/β-catenin pathway

Abstract: Proliferation of the neural/neuronal progenitor cells (NPCs) at the ventricular zone of the dorsal spinal cord requires the stimuli of Wnt and bone morphogenic protein (BMP). However, how these two signaling pathways are regulated to initiate differentiation in the NPCs as they enter the intermediate zone is not known. Here, we show that Smad6, a negative regulator of BMP signaling, is expressed in the intermediate zone of the chick dorsal spinal cord. Knockdown experiments show that Smad6 is required for prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…On the one hand, Xie and colleagues (Xie et al, 2011) found that, in the dorsal spinal cord, Smad6 promotes neuronal differentiation by repressing the Wnt canonical pathway, and thus resulting in the reduced proliferation rate of neural progenitors. On the other hand, Hazen and colleagues (Hazen et al, 2011) showed that electroporation of Smad6 or Smad7, at the time of dIN neurogenesis, results in a reduction of dI1 and dI3, without the compensatory increase of dI4 neurons.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Xie and colleagues (Xie et al, 2011) found that, in the dorsal spinal cord, Smad6 promotes neuronal differentiation by repressing the Wnt canonical pathway, and thus resulting in the reduced proliferation rate of neural progenitors. On the other hand, Hazen and colleagues (Hazen et al, 2011) showed that electroporation of Smad6 or Smad7, at the time of dIN neurogenesis, results in a reduction of dI1 and dI3, without the compensatory increase of dI4 neurons.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, emerging neural crest cells express CtBP2, whereas dorsal root ganglia express CtBP1 (84). The importance of CtBP expression during avian CNS development is highlighted by the key involvement of these proteins in regulating the transition of neural precursor cells in the ventricular zone of the dorsal spinal cord from a proliferative to a differentiated state (85). Furthermore, as previously mentioned, CtBPs appear to have an important role in neural tube closure and development of the forebrain and hindbrain in mice (6).…”
Section: Ctbps and Cns Developmentmentioning
confidence: 99%
“…Thus, monitoring the position of electroporated cells by evaluating EGFP expression together with that of HuC/D serves to assess neurogenesis in vivo ( Fig. 2A) (García-Campmany and Martí, 2007;Xie et al, 2011). When analyzed 48 hours post electroporation (hpe) of either control (pCIG) or Smad2, EGFP + cells were evenly distributed throughout the ventricular zone and the mantle zone (HuC/D + cells: Fig.…”
Section: Smad2 and Smad3 Cooperate And Act As Antagonists In Neurogenmentioning
confidence: 99%